2015
DOI: 10.5761/atcs.oa.14-00218
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Surgically Resected N2 Non-small Cell Lung Cancer

Abstract: Purpose: Non-small cell lung cancers (NSCLCs) with pathologically documented ipsilateral mediastinal lymph node (LN) metastases (pN2) are a broad spectrum of diseases. We retrospectively analyzed prognostic factors for cases of pN2 NSCLC treated by surgical resection. Methods: Clinicopathological data were reviewed for consecutive 121 patients who underwent anatomical pulmonary resection with mediastinal LN sampling or dissection for pN2 NSCLC over a 15-year period. Results: The 5-year survival rate for all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The specific primer sequences are listed in Table I. MTT assay. A549 cells were seeded at a density of 3x10 4 cells/ml in a 24-well plate, cultured for 24 h and then treated with fisetin (0, 10, 20, 30 or 40 µM for 24, 48 or 72 h). The cell viability was analyzed using an MTT assay according to a previously described method (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific primer sequences are listed in Table I. MTT assay. A549 cells were seeded at a density of 3x10 4 cells/ml in a 24-well plate, cultured for 24 h and then treated with fisetin (0, 10, 20, 30 or 40 µM for 24, 48 or 72 h). The cell viability was analyzed using an MTT assay according to a previously described method (27).…”
Section: Methodsmentioning
confidence: 99%
“…However, >80% of NSCLC patients cannot be treated with surgery due to the high prevalence of metastasis (3). According to statistics, the 5-year survival rate after lung cancer diagnosis is only 17.7% (4). NSCLC commonly develops resistance to radiation and chemotherapy, and patients are often diagnosed at stages beyond surgical remedy (5).…”
Section: Introductionmentioning
confidence: 99%
“…[21] Unforeseen N2 reflects minimal mediastinal invasion and favorable survival. [22,23] In this subgroup, the addition of adjuvant radiotherapy to chemotherapy did not provide extra benefit compared with chemotherapy alone. [24] Minimal N2/single station was regarded as potentially resected cases proposed by the European Society for Medical Oncology (ESMO) Clinical Practice Guidelines.…”
Section: Discussionmentioning
confidence: 84%
“…This group of unexpected mediastinal involvement disease is mostly a single-station mediastinal lymph node metastasis. Some literatures support single-station N2 metastasis as the first choice for surgical treatment [ 44 46 ]. Therefore, it is clinically feasible for this group of patients to continue to perform surgery and receive postoperative adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…With the latest guidelines, for some of the patients of this study, neoadjuvant chemo- and/or radiotherapy would be recommended. However, for the period of the reported study we took into account other reports (see for example [ 45 , 46 ]) which suggest that for cases with small primary tumor and absence of multi-station metastases, additional treatment may be omitted. For T3/T4 cases with N0/N1 status, we concluded that surgery was sufficient without preliminary treatment.…”
Section: Discussionmentioning
confidence: 99%